Implementing a community-based tuberculosis programme in the Omaheke region of Namibia: nurses' perceived challenges - Simbisayi Zvavamwe; Valerie J Ehlers (AOSIS, 2008)
Tuberculosis (TB) is a resurgent disease in many regions of the world, including Namibia, fuelled by poor TB control programmes, human immunodeficiency virus (HIV) and poverty. The purpose of this survey was to identify nurses' perceived challenges in implementing a community-based TB programme in the Omaheke region of Namibia. Structured interviews were conducted with 40 nurses involved in providing TB treatment and care in the Omaheke region. Patient-related challenges which hampered TB treatment included alcohol and drug abuse, poverty and stigma. Lack of transport for nurses to do community-based TB work, centralised TB services and patients' lack of transport were access-related challenges. Knowledge-related challenges involved a lack of TB knowledge by both nurses and community members. The HIV pandemic has increased the number of TB patients and increased nurses' workloads, aggravating the burden of TB as a resurgent disease in this region. Decentralisation of TB care to community and family levels would be necessary to reduce the number of people with active TB in the community, and to enhance the TB cure rates, in the Omaheke region of Namibia. In order to implement a successful communitybased TB programme, the patient-related, access-related and knowledge-related challenges, perceived by the nurses, need to be addressed effectively. Opsomming Tuberkulose (TB) is 'n siekte wat herrys in baie dele van die wêreld, insluitende Namibië, en wat aangevuur word deur swak TB-beheerprogramme, menslike immuniteitsgebreksvirus (MIV) en armoede. Die doel van die opname was om waargenome uitdagings van verpleegkundiges te identifiseer tydens die implementering van 'n gemeenskapsgebaseerde TB-program in die Omaheke-streek van Namibië. Gestruktureerde onderhoude is met 40 verpleegkundiges gevoer wat gemoeid was met TB-behandeling en -versorging in die Omaheke-streek. Pasiëntverwante uitdagings wat TB-behandeling nadelig beïnvloed, sluit alkohol- en dwelmmisbruik asook armoede en stigma in. 'n Gebrek aan vervoer vir verpleegkundiges om gemeenskapsgebaseerde TB-werk te doen, die sentralisasie van TB-dienste en pasiënte se gebrek aan vervoer was die toegangsverwante uitdagings. Kennisverwante uitdagings het die gebrek aan TB-kennis van beide verpleegkundiges en gemeenskapslede ingesluit. Die MIVpandemie het die aantal TB-pasiënte vermeerder en verpleegkundiges se werksladings verhoog, wat die las van TB as 'n herrysende siekte in die streek vererger het. Desentralisasie van TB-sorg tot op gemeenskaps- en gesinsvlak sal nodig wees om die getal mense met aktiewe TB in die gemeenskap te verminder, en om die TB-geneeskoerse in die Omaheke-streek van Namibië te verbeter. Ten einde 'n suksesvolle gemeeskapsge-baseerde TB-program te implementeer, moet die pasiënt-, toegangs- en kennisverwante uitdagings, soos deur die verpleegkundiges waargeneem, effektief oorkom word.